A novel way to engage youth in research: evaluation of a participatory health research project by the international children's advisory network youth council. Issue 1 (31st December 2020) - Tsang, Vivian W. L.; Fletcher, Sarah; Thompson, Charles; Smith, Sharon
ABSTRACT: Background: Little is known about the impact of a participatory approach in adolescent health research and the specific benefits youth derive from such experiences. This study evaluates the benefits and limitations of involving young patients as co-researchers in the creation and execution of an international participatory health research project. Methods: Standardized feedback surveys and qualitative interviews were employed to evaluate the impact of co-researchers' personal and academic growth. Participation was determined by the percentage of youth members actively engaged (75% or more), and outcome of a completed project. Results: 16 adolescents aged 13–23 years representing 9 global academic institutions participated. Eighty-one per cent of participants reported interest in health research and 100% felt that their participation made an impact on paediatric healthcare. Discussion: The shift in roles from patient to research partner is echoed in the strong conviction of the newfound possibilities of accomplishment as a group.